Strategi Layanan Perpustakaan Masjid Gedhe Kauman Yogyakarta di Era Covid-19 - Putri, Monica; Sari, Khoirunnisa Etika (UIN Raden Intan Lampung, 2022)
This study aims to determine the service strategy used by the Gedhe Kauman Yogyakarta Mosque Library in the era of the Covid-19. This study uses a qualitative method with a descriptive approach. Collecting data in this study using interviews, observation, and documentation. Test the validity of this research data using triangulation techniques sources and methods, as well as member check. The data analysis technique used is the theory of Miles & Huberman, namely data reduction, data presentation, and drawing conclusions and verification. The results of this study reveal that the offline service strategy at the Gedhe Kauman Mosque Library is in the form of circulation services by implementing health protocols, and children's services or Kids Corner. Meanwhile, for online library services, there are book pick-up and book consultation services. Based on the results of the analysis, the obstacles to implementing the service strategy during the pandemic are the lack of awareness of the administrators to comply with library service opening times as well as the existence of offline lecture trials from campus which resulted in the administrators not being able to attend according to the picket schedule, and the lack of a collection of books that could be used as reference for college assignments. The solution from the management to overcome problems in carrying out the service strategy regarding Human Resources (HR) is to adjust the picket schedule, while for the lack of book collections, additional collections are proposed through the head of the library.